Applying a Risk-Based Approach to Health Facility Management - S. S. Budarin (Здоровье мегаполиса, 2023)
The article discusses potential applications of a risk-based approach to health facility management. The study analyzed various management models, as well as process-oriented and project-oriented management systems, the use of risk management, quality management standards, lean technologies (lean manufacturing), and scorecard interfaces (score ratings). The article presents the results of applying risk analysis, which was developed using balanced scorecard approach that describes activities of a health facility. It was found that the balanced scorecard approach and scoring calculations enable risk level assessment in a health facility to classify risks by work areas and take suitable measures to mitigate or prevent them.